Evidence-based region of interest matching guidelines for sarcoma volumetric image-guided radiation therapy. (March 2018) - Li, Winnie; Appiah, Samuel; Hill, Christine; Becker, Nathan; Catton, Charles; Chung, Peter; Shultz, David; Ferguson, Peter; O'Sullivan, Brian; Dickie, Colleen
Highlights: Region-of-interest (ROI) guidelines for soft tissue sarcoma CBCT-guidance were developed. ROI guidelines were developed for four anatomic sites using the PDSA cycle. ROI guidelines are intended to increase image registration reproducibility. Results include improved image guidance decision making and workflow efficiencies. Abstract: Purpose: Region-of-interest (ROI) guidelines for online cone-beam computed tomography (CBCT) radiotherapy may improve matching reproducibility and reduce inter-user variability of soft tissue sarcoma (STS) image guidance. The purpose of this work is to standardize ROI STS CBCT image registration guidelines using the plan-do-study-act (PDSA) cycle for the lower extremity, retroperitoneal, pelvis, and thorax. Methods: Based on anatomic bony surrogates, initial ROI matching guidelines for STS were developed by a team of radiation therapists, physicists and oncologists (Plan). Retrospective, qualitative evaluation of the guidelines was completed by the designated sarcoma lead therapist to determine clinical feasibility (Do). Validation of the ROI guidelines was performed through independent evaluation by radiation therapy CBCT imaging experts on a cohort of 10 patients per anatomic region (Study). Results: Draft ROI guidelines were evaluated by 2 independent observers who registered weekly CBCT images to test their validity. Each observer assessed 5 patients per anatomic site, testing ROI options for accuracy of image registration and feasibility, while some ROI borders were adjusted based on algorithm matching performance. Validated ROI guidelines were presented to the sarcoma multidisciplinary site group, and an inter-professional committee of imaging experts for approval prior to clinical implementation (Act). Conclusion: ROI matching guidelines for STS IGRT were standardized for 4 anatomic sites using the PDSA cycle for change testing and implementation. IGRT guidelines are intended to improve STS image registration reproducibility, and in turn, are expected to improve the confidence of IGRT decision making and workflow efficiencies for a rare disease with diverse presentation.